1999
DOI: 10.1007/s004210050600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic bicarbonate ingestion on the performance of high-intensity work

Abstract: We have evaluated whether sodium bicarbonate, taken chronically (0.5 g x kg(-1) body mass) for a period of 5 days would improve the performance of eight subjects during 60 s of high-intensity exercise on an electrically braked cycle ergometer. The first test was performed prior to chronic supplementation (pre-ingestion) while the post-ingestion test took place 6 days later. A control test took place approximately 1 month after the cessation of all testing. Acid-base and metabolite data (n = 7) were measured fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
1
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 18 publications
9
64
1
12
Order By: Relevance
“…An average value was calculated to produce an overall self-efficacy score. Fingertip capillary blood lactate (BLa; Analox Micro-Stat, P-GM7, USA) and blood acid-base status (pH, pO2, pCO2, ctHb, sO2, cBase, cHCO3 -; Radiometer, ABL800, Copenhagen, Denmark) were analysed prior to each trial and the participants' hand was warmed prior to sampling to ensure an accurate reflection of an arterialised capillary sample (27).…”
Section: Pre-trial Measuresmentioning
confidence: 99%
“…An average value was calculated to produce an overall self-efficacy score. Fingertip capillary blood lactate (BLa; Analox Micro-Stat, P-GM7, USA) and blood acid-base status (pH, pO2, pCO2, ctHb, sO2, cBase, cHCO3 -; Radiometer, ABL800, Copenhagen, Denmark) were analysed prior to each trial and the participants' hand was warmed prior to sampling to ensure an accurate reflection of an arterialised capillary sample (27).…”
Section: Pre-trial Measuresmentioning
confidence: 99%
“…Studies have shown that 0.3 g/kg bicarbonate and 0.3-0.5 g/kg citrate taken orally with 1-2 L of water 60-90 min pre-exercise increases the pH in the extracellular space (McNaughton 2000). Higher doses spread over a day or so may have prolonged effects, including improved training duration (McNaughton et al 1999). These changes have shown performance enhancement in high intensity exercise (either 1-7 min continuous or 30-60 min intermittently) (Burke 2007).…”
Section: Nutrient Intake For Anaerobic Exercisementioning
confidence: 97%
“…Contudo, apenas um estudo apresentou resultados positivos, com uma grande melhora de 25% no desempenho aeróbio (AZEVEDO et al, 2007). No entanto, como há aumento dos níveis de pH (FAHEY et al, 1991;MORRIS, et al, 2011;PAINELLI et al, 2014) e bicarbonato (FAHEY et al, 1991;PAINELLI et al, 2014) (MCNAUGHTON, et al, 1999), pois pode promover um incremento maior no bicarbonato sanguíneo com o maior período de suplementação, mas esse protocolo ainda precisa ser explorado. Os dados estão apresentados como média ± desvio-padrão.…”
Section: Suplementação De Bicarbonatounclassified